PENGARUH FINANCIAL PRESSURE, SISTEM PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI DAN KOMITMEN ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA LEMBAGA PERKREDITAN DESA - Kadek Sinta Santika; Ni Putu Budiadnyani; Gine Das Prena; Putu Sri Arta Jaya Kusuma (ITB AAS Indonesia, 2025)
A lot of news has spread regarding fraud cases that have occurred in Village Credit Institutions (LPD), thus making people's views on LPDs decline. The purpose of this study was to determine the effect of financial pressure, internal control system, compliance with accounting rules and organizational commitment on the tendency of accounting fraud in LPDs. This type of research is quantitative research. Data obtained from distributing questionnaires directly. The population used is all LPD employees in Badung Regency who are registered in the Badung Regency LPLPD. The sampling technique in this study used purposive sampling technique. By using a sample of 49 LPDs with 180 LPD employee respondents. Data analysis in this study used descriptive analysis, instrument test, classical assumption test, multiple linear regression analysis and hypothesis testing with the help of the SPSS program. The results of this study indicate that financial pressure has a significant positive effect on the tendency of accounting fraud, the internal control system has a significant negative effect on the tendency of accounting fraud, the observance of accounting rules has a significant negative effect on the tendency of accounting fraud, and organizational commitment has a significant negative effect on the tendency of accounting fraud.